(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2022)
Purpose: Africa has a very low rate of induction of labour with high maternal and perinatal morbidity and mortality. However fetal-maternal outcomes following induction of labour are not well documented in Tanzania. This study aimed to assess fetal-maternal outcomes following induction of labour among women delivered at Dar es Salaam regional referral hospitals in Tanzania. Design/methodology/Approach: A total of 301 expectant mothers were recruited in a prospective observational study conducted at all regional referral hospitals in Dar es Salaam, Tanzania. Data on fetal-maternal outcomes were collected using a pre-designed clinical sheet. Demographic data, obstetric history, methods as well as outcomes of labour induction were recorded. The continuous variables were summarized using the median and corresponding interquartile range. Categorical variables were summarized using frequency and proportions and the significance of differences were assessed using Chi-square at P<0.05. Results: The leading methods for induction of labour were Oxytocin (48.5%) and a combination of Folley’s catheter with Oxytocin (28.4%). Induction of labour significantly improved fetal outcomes at birth P<0.05. Induction of labour associated with improved Apgar scores in newborn babies. Failure of induction of labour was the largest contributor to the increased Caesarean Section rate observed in this study. Research limitation/Implication: This study has therefore explored the fetal-maternal outcomes following induction of labour in Tanzanian regional referral hospitals. Practical implication: Induction of labour improves and minimizes neonatal complications in referral regional hospitals in Dar es Salaam. Originality/Value: These findings fill a gap of information which was missing on the fetal-maternal outcomes following induction of labour among expectant mothers in Dar es Salaam regional referral hospitals.